- 11


x(k) := xmn x(k) = xmn

next k

return

 

4. ,

(1)' £ (2)' £ ... £ x(N)'

L[1:N],

x(k)' = p(L(k)) k = 1, .... N.

. ­ (1)' £ (2)' £... £ x(N)' x[l:N] . :

 

Imn := L(imn) Imn = L(imn)

xmn

:= x(imn) xmn = x(imn)

L(imn) := L(k) L(imn)' = L(k)

x(imn) := x(k) x(imn)' = x(k)

L(k) := Imn L(k)' = Imn = L(imn)

x(k) := xmn x(k)' = xmn = x(imn)

 

L[1:N] ­ x[l:N] , ­ :

(i)' = P(L(i) i = 1, ..., N.

, . , k- :

 

Imn = L(imn)

xmn = x(imn) == p(L(imn))

L(imn)' = L(k)

x(imn)' = x(k) = p(L(k)) = p(L(imn)')

L(k)' = Imn = L(imn)

x(k)' = xmn = x(imn) = p(L(imn)) = p(L(k)')

 

,




- -  - -  - -